2023
DOI: 10.1038/s41598-023-43509-9
|View full text |Cite
|
Sign up to set email alerts
|

The application of high-performance ultrasound probes increases anatomic depiction in obese patients

Sascha Heinitz,
Jürgen Müller,
Klaus-Vitold Jenderka
et al.

Abstract: This study evaluated the impact of obesity on abdominal ultrasound diagnostics and assessed effect of high-performance ultrasound probes increased imaging quality. Lean and obese subjects (n = 40; 58% female) were categorized according to body mass index (BMI, 21 to 48 kg/m2). A highly standardized ultrasound examination of the abdomen was performed by trained examiners using three different probes in randomized order (standard probe versus two high-performance probes). Quality of B-mode and duplex ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This was comparable to our study. However, in our study, the latter subgroups also showed a multitude of structural anomalies with a higher frequency than in other studies (40), indicating the high sensitivity of the applied US methods (44). Consistent with recent studies (9,10,11), our results support the milder renal involvement in patients with BBS1 mutations.…”
Section: Renal Involvementsupporting
confidence: 92%
“…This was comparable to our study. However, in our study, the latter subgroups also showed a multitude of structural anomalies with a higher frequency than in other studies (40), indicating the high sensitivity of the applied US methods (44). Consistent with recent studies (9,10,11), our results support the milder renal involvement in patients with BBS1 mutations.…”
Section: Renal Involvementsupporting
confidence: 92%
“…However, our study was limited to healthy volunteers with normal BMIs (see Supplementary Table 2 ). Therefore, the observed differences might be more pronounced for more demanding ultrasound investigations, like in obese patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…With obesity becoming a global epidemic, this is especially useful. Ultrasound signal gets attenuated and scattered as tissue thickness increases, especially adipose (Glanc et al, 2012;Uppot, 2018;Heinitz et al, 2023). Real-time imaging is being developed by utilizing fast scanning mechanisms and lasers with higher repetition rates (Manwar et al, 2018;Jeon et al, 2019;Kim et al, 2020a).…”
Section: Discussion and Outlookmentioning
confidence: 99%